Processing power sharing using a gadget 'Power Save' for downloading scientific research projects. Issue 3 (3rd October 2022) - Taywade, Akshay; Sasikala, R.
In today's era users had become more uphill and expect to run compute-intensive apps in their smartphone devices. Mobile Cloud Computing (MCC) thus combines mobile computing and Cloud Computing (CC) in order to use offloading techniques to expand mobile computer capabilities. Computer offloading solves Smart Mobile Devices (SMD) limitations such as limited computing power, limited battery life and limited storage space by distributing output and workload to other rich systems with enhanced efficiency and resources. For data modelling and analysis, scientific research also needs a large amount of computing power. This paper explains about the donation of processing power from unused smartphone computing power to the mobiles that need to download projects of medicine, astronomy, geology and physics through mobile web services. This is accomplished by developing a cellular gadget called 'Power Save' that download and coordinate the projects to be downloaded during the dormant condition of the mobile. Once the project is downloaded, the status of project server is changed and a new task is assigned. This gadget-based processing power sharing would be assistive in saving mobile's battery life and performance level of CPU. The proposed gadget is compared against certain existing applications such as HTC power to give BOINC.